Total Bacterial Load within Echinacea purpurea, Determined Using a New PCR-based Quantification Method, is Correlated with LPS Levels and In Vitro Macrophage Activity - Pugh, Nirmal D.; Jackson, Colin R.; Pasco, David S. (Planta Medica, 2013)
Our previous studies indicate that the majority of in vitro monocyte/macrophage activation exhibited by extracts of Echinacea depends on bacterial components. In the present study, total bacterial load was determined within E. purpurea samples and ranged from 6.4 × 106 to 3.3 × 108 bacteria/g of dry plant material. To estimate total bacterial load, we developed a PCR-based quantification method that circumvents the problems associated with nonviable/nonculturable cells (which precludes using plate counts) or the coamplification of mitochondrial or chloroplast DNA with the use of universal bacterial primers (which precludes the use of qPCR). Differences in total bacterial load within Echinacea samples were strongly correlated with the activity (NF-κB activation in THP-1 cells) and content of bacterial lipopolysaccharides within extracts of this plant material. These results add to the growing body of evidence that bacteria within Echinacea are the main source of components responsible for enhancing innate immune function.
Keywords: Echinacea purpurea; Asteraceae; macrophage activation; lipopolysaccharide; bacteria; bacterial load; PCR method